A Case Study of Brick Properties Manufacture in Bhaktapur - Shrestha, Shova (Journal of Science and Engineering, 2019)
Bricks are commonly used for construction of buildings structures. The main objective of this article is to present the case study on different properties of the bricks manufactured in Bhaktapur city. Sample specimens were collected and tested for crushing strength, water absorption, specific gravity, density, porosity, impact test, dimension test, hardness test, soundness test and color appearance test of bricks in the laboratory. The overall aim of this study is to determine, through extensive experimental investigation, the effect of different brick on strength, water absorption, density, hardness, impact, porosity, and crushing strength. After multiple tests, results regarding the properties of bricks included – water absorption varies from 8.80% to 23.93%, porosity varying from 19.28% to 53.99%, specific gravity varying from 2.19 to 4.00, density varying from 1549.77 kg/m3 to 2816.6kg/m3, and crushing strength varying from 7.83 MPa to 22.10 MPa. In hardness test, 15 out of 33 were found to be hard; while 13 out of 33 passed the impact test; and 18 out of 33 has metallic sound. For the good quality of brick, the brick should have bright color appearance but only 15 out of 33 samples carry bright color appearance. Regarding the dimensions, length varies from 212.00 mm to 242.00 mm, breadth varies from 96.00 mm to 115.00 mm and thickness varies from 48.80 mm to 63.00 mm. From this research, properties of almost all bricks are not as per Nepal Building Code. The bricks manufactured at present are being commercialized rather than maintaining the standards as per the code.